FAKTOR-FAKTOR YANG MEMPENGARUHI IMPULSE BUYING PRODUCT PADA PEMBELI MINIMARKET - Khalimah, Khalimah; Prabowo, Heri (JAB (Jurnal Akuntansi & Bisnis), 2017)
The purpose of this research was to found the influence: (1) effect of pricediscount on impulse buying of minimarket Indomaret customer, (2) effect ofbonus pack on impulse buying of minimarket Indomaret customer, (3) effect of price discount and bonus pack on impulse buying of minimarket Indomaret customer. This research was conducted based on associative research. Population of this research were consumer of minimarket Indomaret in St. Demangan Baru, Depok, Sleman, Yogyakarta. Purposive sampling was used as a sampling methode with the total sample of 170 people. Data was collected through question naire which validity and reliability were already verified. Multiple regression was used as analysis technique. Results have show that: (1) there was positive effect of price discount on impulse buying of minimarket Indomaret customer by t= 7,806 with significance value of 0,000<0,05 and positive value of regression coefficient which was 0,743; (2) there was positive effect of bonus pack on impulse buying of minimarket Indomaret customer by t= 3,866 with significance value of 0,000<0,05 and positive value of regression coefficient which was 0,289; (3) there was effect of price discount and bonus pack on impulse buying of minimarket Indomaret customer of F count= 47,327 with significance value of 0,000<0,05.Keyword: Price Discount, Bonus Pack, Impulse Buying, Minimarket